The Vytis in New Contexts: How does the Changing Use of the Symbol Relate to the Temperature of Nationalism? - Gimbutaitė, Monika (Politologija, 2022)
The Vytis (Coat of Arms of Lithuania) is a national symbol of Lithuania that typically functions within an official state frame. This paper examines how the use and functions of the Vytis had changed from the year 2013 to 2019. While presenting an analysis of the new forms of Vytis expression, a question arises: how does the intensified and atypical use of the symbol correlate with the temperature of nationalism in our society? The research, which is based on discourse theory and includes visual and textual information found in media, social media, and other non-academic platforms, allows distinguishing four new directions of the symbol’s expression: (1) commercialization, (2) transformation into a political tool, (3) transfer to everyday culture, and (4) individual practices as well as creative practices. This paper concludes that the changing use of Vytis shows elements of both cooling and heating nationalisms. We face a cooling nationalism when the symbol becomes a part of a routine that we no longer reflect. We can also detect attributes of heating nationalism in our society. They are triggered by a sense of internal or external threats and are inseparable from the temperature of our public space.
Keywords: Coat of Arms of Lithuania; national symbols; banal nationalism; temperature of nationalism; heating nationalism; cooling nationalism